Time-dependent effects of prone position on ventilation-perfusion matching assessed by electrical impedance tomography in patients with COVID-19 ARDS: sub-analysis of a prospective physiological study - Yuxian Wang; Yaxiaerjiang Muhetaer; Xin Zheng; Wei Wu; Jiale Tao; Ling Zhu; Jieqiong Song; Zhanqi Zhao; Ming Zhong (Annals of Intensive Care)
Abstract Background Prone positioning (PP) has been shown to improve oxygenation in patients with acute respiratory distress syndrome (ARDS); with a focus on its early physiological effects. However, the time-dependent effects of PP on ventilation-perfusion (V/Q) matching have not been fully investigated. In this study we aimed to investigate the longitudinal effects of PP on regional V/Q matching and the distribution of ventilation and perfusion in patients with coronavirus disease 2019 (COVID-19)-associated ARDS. Methods This study analyzed patients with COVID-19 ARDS who were mechanically ventilated and underwent their first PP treatment. V/Q mismatching was assessed using electrical impedance tomography (EIT). At five intervals during the initial PP session PaO2/FiO2 measurements and EIT evaluations were performed including: before the initiation of PP while in the supine position (SP), 1 h after PP (PP1), 3 h after PP (PP3), 16 h after PP (PPend), and 3 h after reverting to the supine position (RE-SP3). Results In this study eighteen COVID-19 ARDS patients were enrolled. In comparison with SP, PP led to significant improvements in oxygenation, with PaO2/FiO2 consistently increasing at each PP time point and peaking at PPend. Dorsal ventilation significantly increased at PP1 (P = .047), and steadily rose during PP, with a higher increase at PPend than PP1 (P < .001). Dorsal perfusion remained unchanged during the first three hours of PP; however, significantly increased by PPend. Ventilation and perfusion returned to their baseline levels at RE-SP3. PP increased normal V/Q (%), and decreased non-perfused (%), low V/Q (%), particularly in the dorsal lung regions, compared with SP. At RE-SP3, there was a marked increase in the non-ventilated (%), low V/Q (%), and non-perfused (%) compared with PP. The global inhomogeneity (GI)-V/Q ratio was noted to have decreased during PP and correlated with an increase in PaO2/FiO2. Conclusions In COVID-19-induced ARDS patients, prone positioning initially improves oxygenation and V/Q matching by enhancing ventilation distribution and decreasing low V/Q (%). Over time, perfusion changes further improve V/Q matching, but these benefits diminish once the patient returns to the supine position, leading to increased V/Q mismatch. Trial registration Clinical Trials.gov, NCT04725227. Registered 25 January 2021, https://clinicaltrials.gov/study/NCT04725227?cond=NCT04725227&rank=1